Estudo da influência da composição em materiais compósitos de polipropileno com fibras de vidro por pultrusão termoplástica nas propriedades mecânicas - Lima, Amanda Santos de (2024)
The objective of this work is to evaluate manufacture variations over thermoplastic composite materials of polypropylene reinforced with glass fibers (FV) regarding their tensile and flexural mechanical properties (PMs). The samples are produced by a partner company located in São Carlos - SP, Brazil, and manufacture variation are as described: geometry of the heated die (pin, MP, and waves, MO), the use and the position of the conformer (d = 0 of the heated die, upper part of the conformer at d = 0 and the lower part at a distance “d” and completely away at a distance “d”), pulling speed (7 and 15 m/min), fibers with different surfaces and different concentrations of maleic anhydride (MA). The results show that the crystallinity of the materials was influenced by geometry of the heated die (MP ~ 28% and MO = 39%). The position of the conformer was shown to influence the PMs and the crystallinity, which the material C2.O1122-CM, at position d = 0, had the lowest tensile (73 MPa) and flexural (67 MPa) values and the highest crystallinity value (~35%) within the sample of the group with conformer. Through the optical microscopy it shows that the conformer did not perform well on providing a cylindrical and uniform pellet. The variations of pulling speed showed that it influences crystallinity (C2.O115 ~ 34% and C2.O215 ~ 30%) but there is no difference in PMs. Through a multivariate analysis of the group of the samples with variation of FV and MA, it was possible to observe the influence of each variable on the PMs and verify that the best condition was achieved with an intermediate FV texture and lower concentration of MA with the sample C2.O212 (tensile ~ 91 MPa and flexural = 163 MPa).